The genome of the largest bony fish, ocean sunfish (Mola mola), provides insights into its fast growth rate. Issue 1 (9th September 2016) - Pan, Hailin; Yu, Hao; Ravi, Vydianathan; Li, Cai; Lee, Alison P.; Lian, Michelle M.; Tay, Boon-Hui; Brenner, Sydney; Wang, Jian; Yang, Huanming; Zhang, Guojie; Venkatesh, Byrappa
Abstract: Background: The ocean sunfish ( Mola mola ), which can grow up to a length of 2.7 m and weigh 2.3 tons, is the world's largest bony fish. It has an extremely fast growth rate and its endoskeleton is mainly composed of cartilage. Another unique feature of the sunfish is its lack of a caudal fin, which is replaced by a broad and stiff lobe that results in the characteristic truncated appearance of the fish. Results: To gain insights into the genomic basis of these phenotypic traits, we sequenced the sunfish genome and performed a comparative analysis with other teleost genomes. Several sunfish genes involved in the growth hormone and insulin-like growth factor 1 (GH/IGF1) axis signalling pathway were found to be under positive selection or accelerated evolution, which might explain its fast growth rate and large body size. A number of genes associated with the extracellular matrix, some of which are involved in the regulation of bone and cartilage development, have also undergone positive selection or accelerated evolution. A comparison of the sunfish genome with that of the pufferfish (fugu), which has a caudal fin, revealed that the sunfish contains more homeobox (Hox) genes although both genomes contain seven Hox clusters. Thus, caudal fin loss in sunfish is not associated with the loss of a specific Hox gene. Conclusions: Our analyses provide insights into the molecular basis of the fast growth rate and large size of the ocean sunfish. The high-quality genome assembly generated in this study should facilitate further studies of this 'natural mutant'.